Synthesis and Biological Evaluation of Pyrrole-Imidazole Polyamide Probes for Visualization of Telomeres - Kawamoto, Yusuke (Springer Theses, Recognizing Outstanding Ph.D. Research, 2019)
This book presents a novel method of synthesizing sequence-specific DNA binding pyrrole-imidazole (Py-Im) polyamides and demonstrates polyamides targeting longer base pairs than those previously reported and their cellular application. It discusses the development of the facile synthetic method of tandem hairpin Py-Im polyamides and the method of visualizing telomeres under mild conditions without harsh denaturation, as well as research resulting in the synthesis not only of previously reported tandem dimer polyamides but also longer tandem trimer and tetramer polyamides. Using fluorescently labeled tandem hairpin Py-Im polyamides targeting a human telomere repetitive sequence, the author successfully stained telomeres in fixed cells without denaturation. These fluorescently labeled tandem tetramer polyamides are able to visualize human telomeres with lower background signals than previous polyamide probes, suggesting that they have higher specificity for telomeres. As such, this bookprovides insights into recent advance in Py-Im polyamides, particularly the extension of the target sites and improvement of the specificity, which can be applied to the study of pyrrole-imidazole polyamides with higher sequence specificity and the function of telomeres.